2004
DOI: 10.1128/jcm.42.8.3752-3757.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Nosocomial and Native American Community-Associated Methicillin-ResistantStaphylococcus aureusClones from Rural Wisconsin

Abstract: In central and northern Wisconsin methicillin-resistant Staphylococcus aureus (MRSA) was first detected in 1989. Over the next 10-year period, 581 MRSA isolates were collected, 17.2% of which came from patients who were treated at five Native American clinics. These isolates were typed by SmaI-macrorestricted pulsed-field gel electrophoresis (PFGE). The PFGE patterns clustered the isolates into six major clonal groups (MCGs), i.e., MCGs 1 to 6, and 19 minor clonal groups (mCGs). The 25 clonal groups were repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
51
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 42 publications
9
51
1
Order By: Relevance
“…In contrast to CA-MRSA epidemiology described as homogeneous in Australia (13), some parts of the United States (14), or Sweden (15), our local epidemiology appears more heterogeneous.…”
Section: Discussionmentioning
confidence: 40%
“…In contrast to CA-MRSA epidemiology described as homogeneous in Australia (13), some parts of the United States (14), or Sweden (15), our local epidemiology appears more heterogeneous.…”
Section: Discussionmentioning
confidence: 40%
“…and E. coli that are expected to be absent were positive indications of the risks posed by the use of herbal preparations. Therefore, the high recovery rates of these suspected infectious bacteria from indigenous orally consumed herbal medications could be of clinical relevance (Shukla et al, 2004). Abba et al (2008) in their study on herbal preparations found almost similar results.…”
Section: Discussionsupporting
confidence: 57%
“…Studies mostly focus on methicillin-resistant S. aureus (MRSA), due to its clinical importance. In fact, most Community-Acquired (CA)-MRSA clones contain PVL genes and the rates were 70% to 100% Shukla et al, 2004;Naas et al, 2005). Not only MRSA strains, but also MSSA strains, which were isolated from skin and soft-tissue infections, were found to carry PVL genes (Moran et al, 2006).…”
Section: Introductionmentioning
confidence: 99%